Patient relevant endpoints in oncology: Current issues in the context of early benefit assessment in Germany - Inna Dabisch; Jürgen Dethling; Charalabos-Markos Dintsios; Melanie Drechsler; Daniel Kalanovic; Peter Kaskel; Frank Langer; Jörg Ruof; Thorsten Ruppert; Daniel Wirth (Health Economics Review, 2014)
The German AMNOG healthcare reform includes a mandatory early-benefit-assessment (EBA) at launch. As per German social code, EBA is based on registration trials and includes evaluation of the patient-relevant effect of the new medicines compared to an appropriate comparator as defined by the Federal Joint Committee (G-BA). Current EBA decisions released have unveiled issues regarding the acceptance of some patient-relevant endpoints as G-BA and IQWiG are grading the endpoints, focusing on overall survival as the preferred endpoint in oncology. A taskforce of experienced German outcomes research, medical, health-technology assessment and biostatistics researchers in industry was appointed. After agreement on core assumptions, a draft position was prepared. Input on iterative versions was solicited from a panel of reviewers from industry and external stakeholders. Distinctive features of registration trials in oncology need to be considered when these studies form basis for EBA, especially in cancer-indications with long post-progression survival; and with several consecutive therapeutic options available post-progression. Ethical committees, caregivers and patients often demand cross-over-designs diluting the treatment-effect on overall survival. Regulatory authorities require evaluation of morbidity-related study endpoints including survival of patients without their disease getting worse (i.e., progression-free survival). Also, progression requires treatment-changes, another strong indicator for its relevance to patients. Based on specific guidelines and clinical trial programs that were developed to be consistent with regulatory guidance, endpoints in oncology are thoroughly evaluated in terms of their patient-relevance. This extensive knowledge and experience should be fully acknowledged during EBA when assessing the patient-relevant benefit of innovative medicines in oncology.
Keywords: D61; H51; I18; 330; AMNOG; German health care reform; Oncology; Endpoints; Progression-free survival; Patient-relevant benefit